Local model of plane acoustic waves propagation in multilayered infinite sandwich structures - Karczmarzyk, S. (Archives of Mechanics, 2011)
A local model for computing the coincidence frequencies and the transmission loss of multilayered infinite sandwich plates composed of isotropic layers is presented in the paper. The model is derived within the local theory of linear elastodynamics under assumption that only one component of the vector potential is equivalent to zero and after application of the Pythagorean theorem. Any simplifications concerning the structure have not been introduced. A passage from the acoustic model to some plate benchmark models is shown. Numerical results predicted by the model for homogeneous, three-layer sandwich and five-layer sandwich infinite-infinite plates are obtained and compared with the results predicted by other models existing in the literature. Both flexural and breathing waves are numerically analysed. Some conclusions of practical importance have also been formulated.